Analysis of the Effect of Parking on Road Bodies on Road Service Levels. Issue 1 (May 2021) - Akbar, M; Paresa, J; Pamuttu, D L
Abstract: The city of Merauke is now one of the fastest cities in Papua Province. Along with the high urban accessibility, the city of Merauke is also included as a city with heavy traffic. Business Complex cannot be separated from the pull of traffic movement, often causing traffic jams, one of which is caused by the presence of illegal parking on the street (on-street parking). This research was conducted on primary road qualifications, namely the Mandala highway. The purpose of this study was to determine the level of road service and the degree of saturation and the effect of road performance services due to on-street parking. Research methods conducted include a volume survey with traffic counts and parking observations. The calculation uses the 1997 Indonesian Road Capacity Manual (MKJI). Based on the results of calculation traffic volume on weekdays during peak hours under normal conditions, the service level B (0.21-0.44). From the results of these calculations indicate that the performance of the Mandala Highway is classified as busy traffic. Whereas on weekdays with the condition that there is on-street parking, the service level decreases to C (0.45-0.74) in five hours during busy times. The results of this calculation indicate that the performance of the Mandala Highway will decrease by one level if there is parking on the road body (on-street parking).